2005
DOI: 10.1002/cvde.200406351
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Silver Thin Films Using the Pyrazolate Complex [Ag(3,5‐(CF3)2C3HN2)]3

Abstract: The synthesis and characterization of a series of silver pyrazolate complexes [Ag(tfpz)] 3 (1), [Ag(fbpz)] 3 (2), [Ag(dbpz)] 3 (3), and [(py)Ag(tfpz)] 2 (4) are reported, for which tfpz, fbpz, dbpz are abbreviations for the pyrazolate ligands with formulae 3,5-(CF 3 ) 2 -pz, 3-t Bu-5-(CF 3 )-pz, and 3,5-( t Bu) 2 -pz, respectively. These silver complexes were characterized by microanalysis and spectroscopic methods. The CF 3 -substituted complex 1 possesses the highest volatility and stability against thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…The synthesis of Cu(I) and Ag(I) metal organic complexes is commonly achieved by reacting a transition metal salt with the desired oxidation state with a combination of an anionic ligand and a -donor ligand in a one-pot reaction followed by purification [163][164][165][166][167][168][169][170][171][172][173][174][175][176][177][178]. Similarly, Cu(II) MC precursors are obtained in an analogous manner from Cu(II) salts [179][180][181][182].…”
Section: Metal Complexes Applicable To Inkjet Ink Formulationsmentioning
confidence: 99%
“…The synthesis of Cu(I) and Ag(I) metal organic complexes is commonly achieved by reacting a transition metal salt with the desired oxidation state with a combination of an anionic ligand and a -donor ligand in a one-pot reaction followed by purification [163][164][165][166][167][168][169][170][171][172][173][174][175][176][177][178]. Similarly, Cu(II) MC precursors are obtained in an analogous manner from Cu(II) salts [179][180][181][182].…”
Section: Metal Complexes Applicable To Inkjet Ink Formulationsmentioning
confidence: 99%
“…According to the literature, the thermally most stable and sufficiently volatile silver compounds used for CVD of silver seem to be phosphine-adducted carboxylates, pyrazolates, and b-diketonates. [40][41][42] Of these, Ag(O 2 C t Bu)(PEt 3 ) and Ag(O 2 C t Bu)(PBu 3 ) provide a ref-…”
Section: Introductionmentioning
confidence: 99%
“…Many silver complexes have been investigated as suitable precursors for the deposition of silver metal on metallic substrates, but only few show air and moisture stability and decomposition temperatures suitable for a convenient annealing. It was also found that, in some cases, the silver deposition that occurs by CVD may require the stabilization of the precursor by appropriate fictionalization of the ligand …”
Section: Introductionmentioning
confidence: 99%